Artikel Kehormatan: Urgensi Pengaturan Desa dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 (Faculty of Law, Padjadjaran University, 2017)
Artikel ini membahas dua topik penting, pertama, apakah Pasal 18B UUD 1945 belum mengakomodir desa di dalamnya? Kedua, apa urgensi pengaturan desa di dalam UUD 1945? Penelitian ini menggunakan pendekatan filosofis dan perundang-undangan. Analisis terhadap bahan hukum dilakukan secara deskriptif kualitatif. Hasil penelitian menyimpulkan bahwa, pertama, Pasal 18B UUD 1945 belum mengakomodir desa di dalamnya, karena yang diatur di dalamnya hanyalah kesatuan masyarakat hukum adat yang berbeda dengan desa. Kedua, urgensi pengaturan desa dimasukkan dalam UUD 1945 untuk memberikan dasar konstitusional yang lebih kuat bagi desa, karena sesungguhnya desa adalah cikal bakal yang membentuk negara. Di samping itu, untuk menjaga agar eksistensi desa tidak berubah-ubah mengikuti langgam politik kekuasaan.The Urgency to Regulate Administrative Village in the 1945 Constitution of Republic of IndonesiaAbstractThis article will discuss two important topics, first, to elaborate whether Article 18B of the 1945 Constitution of Republic of Indonesia has regulated administrative village; and second, what is the urgency to regulate administrative village in the 1945 Constitution. This research used philosophical approach and legislative provisions. The analysis on legal materials will be performed in the descriptive and qualitative method. The research concludes that first, Article 18B of the 1945 Constitution has not accommodated administraive village, since it only regulates Adat law communities which is different from administrative village. Second, it is urgent to regulate administrative village in the 1945 Constitution in order to strengthen the constitutional fundamental for administrative village, since historically villages are the basis of the establishment of a state. Furthermore, a constitutional fundamental will ensure that the existence of administrative village will not be abruptly affected by the change in political power.Keywords: village, constitution, Article 18B of the 1945 Constitution, adat law communities, local government. DOI: https://doi.org/10.22304/pjih.v4n1.a1